Long-term Follow-up Study for Fractured and Non-Fractured Hand Enchondromas Treated by Sole Curettage - Prahm, Cosima; Kefalianakis, Laura; Heinzel, Johannes; Kolbenschlag, Jonas; Daigeler, Adrien; Lauer, Henrik (Archives of Plastic Surgery, 2025)
Background Enchondromas are the most common primary tumors in the small tubular bones of the hand, and fractures are often the result of thinned cortical bone. The main question was whether fractured enchondromas influence long-term clinical and radiological outcomes.Methods Between 2000 and 2019, 57 patients with previously treated fractured (group I) and non-fractured (group II) hand enchondromas (34 female, 23 male; mean age 39.4 ± 13.7 years) were evaluated for clinical and radiological treatment outcomes. Short Form-36 Health Survey (SF-36) and Disabilities of the Arm Shoulder and Hand (DASH) questionnaires as well as patient-reported experience measures were used to assess subjective health outcomes. Subsequently, 43 patients underwent clinical and radiological follow-ups. Comparative evaluation of objective treatment outcomes in both groups was conducted in terms of hand functionality, perioperative complications, recurrence rates, and osteogenesis.Results Almost half of the patients suffered enchondromas with fractures (49.1%, n = 28). Two patients received additional k-wire stabilization due to intraoperative instability. Defect resolution could be reached in 97.7% (n = 42) of all cases. No recurrence of enchondroma was observed. Groups were equal regarding radiological and clinical outcomes. The patient-reported experiences were predominantly positive (86%), and both cohorts had good to very good results with a DASH mean score of 4 (± 6.3). The SF-36 demonstrated a return to normal quality of life in both groups. The mean follow-up time was 7.78 years (± 4.8).Conclusion Sole curettage of enchondromas yields effective outcomes with good to excellent results regardless of the presence of a fracture. Long-term radiological follow-up is not required until symptomatic recurrence.
Keywords: enchondromas; hand tumors; radiological monitoring; bone augmentation; sole curettage